Kajian Pola Aliran di Hilir Pintu Sorong dengan Material Dasar Saluran Pasir Lempung - Rustiati, N.B.; Suciani, N. (Civil Engineering Department, Tadulako University, 2022)
The operation of a damaged (jammed) sluice result unsuitable velocity distribution with the design. This causes turbulence of the flow which results the hydraulic jump. The hydraulic jumps as a function of energy absorbers. The large energy will cause damage to the water structure. Therefore, there is a need for research to obtain flow profiles. The aims of the research is to investigate the flow characteristic and hydraulics jump that occurred at downstream of manually moving of sluice gate. The height of opening gate set up variated at 0.4 cm to 1.4 cm. The range of using variated discharge from 0.108 lt/s to 0.524 lt/s. The result of investigation showed that the higher of opening gate at the same discharge value the hydraulics characteristic at the downstream of sluice gate decreasing. The hydraulics characteristic are the water depth, hydraulics jump and the flow characteristic. As a results variation discharge and opening gate are subcritical flow.